A new species of trichoglossum (Geoglossales, ascomycota) from Thailand - Anusha H. Ekanayaka (2018)
© 2017 Magnolia Press. The genus Trichoglossum (Geoglossaceae) is characterized by black, clavate, stipitate apothecia with hymenial setae. We collected T. cf. octopartitum from China and a new species of Trichoglossum from Thailand, the latter named as T. septatum. According to morphological examination and molecular phylogenetic analyses of ITS sequence data, T. septatum diverges from other Trichoglossum species. Full descriptions, colour figures, and a phylogenetic tree to show the positions of T. cf. octopartitum and T. septatum are provided, and the two species are compared with allied taxa. The important morphological characteristics of Trichoglossum species are also summarized.